Maintaining research integrity in the age of GenAI: an analysis of ethical challenges and recommendations to researchers - Sonja Bjelobaba; Lorna Waddington; Mike Perkins; Tomáš Foltýnek; Sabuj Bhattacharyya; Debora Weber-Wulff (International Journal for Educational Integrity)
Abstract Background This paper is a practice‑informed rapid review that maps the complex ethical challenges arising from the growing use of Generative Artificial Intelligence (GenAI) tools across the research life‑cycle. Earlier research primarily focused on academic integrity concerns related to students’ use of GenAI tools; however, limited information is available on the impact of GenAI on academic research. This study aims to examine the ethical concerns arising from the use of GenAI across different phases of research and explores potential strategies to encourage its ethical use for research purposes. Methods We selected one or more GenAI platforms applicable to various research phases (e.g. developing research questions, conducting literature reviews, processing data, and academic writing) and analysed them to identify potential ethical concerns relevant for that stage. Results The analysis revealed several ethical concerns, including a lack of transparency, bias, censorship, fabrication (e.g. hallucinations and false data generation), copyright violations, and privacy issues. These findings underscore the need for cautious and mindful use of GenAI. Conclusions The advancement and use of GenAI are continuously evolving, necessitating an ongoing in-depth evaluation. We propose a set of practical recommendations to support researchers in effectively integrating these tools while adhering to the fundamental principles of ethical research practices.